PENDEKATAN METODE SEDIMENT DELIVERY RATIO UNTUK MENGETAHUI TINGKAT KEKRITISAN BEBERAPA SUB DAS DI KALIMANTAN SELATAN DALAM HUBUNGANNYA DENGAN KESESUAIAN PERIKANAN - Sumarni Sumarni; Suhaili Asmawi Asmawi; Abdur Rahman (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Sediment Delivery Ratio Method approach is one method to determine the degree of criticality subzone. The purpose of this study was to determine the amount of erosion that occurs, the critical level of distribution and relationship levels of sediment load to the needs of fisheries in some subzone South Kalimantan.The results of water quality analysis of total suspended solids (TSS) showed thatthe rate of sedimentation (precipitation) is the highest in Sub-watershed area Kusan with arange of about 2918.22 tons / day and the lowest is subject subzone Pelaihari with a range of about 0.64 tons /day. Thus the content of TSS that do not affect the interests of fisheries are at subzone Pelaihari with TSS value of 16 mg/l.